Implementation of the Preference Selection Index (PSI) Method in Determining the Best Coffee Shop - Windarto, Agus Perdana; Mesran, Mesran; Saidah, Fatiyah; Ambarsari, Erlin Windia (Graha Mitra Edukasi, 2024)
The decision support system can be claimed to be a personal computer capable of running data into information so that when taking a semi-structured or problem-specific decision, A coffee shop is a place that prioritizes the sale of coffee with a variety of brewing methods, ranging from cold brew, percolator, Turkish coffee, automatic drip, moka pot, tubruk, Arabica, and many more. In this study, the authors used the PSI (preference selection index) method so that the selection of the best coffee shop was carried out by making a decision matrix, normalizing the decision matrix, calculating the mean value of normalized data, determining the variation of preferences, determining storage in preference values, determining the weight of the criteria, and calculating the PSI value so as to find the best alternative. The criteria used in the selection of coffee shops are five: food, drink, service, entertainment, and parking. Then the final result of the best alternative value is A6 as the best coffee shop in Tanjung Morawa, with a result of 3.702 using the PSI method